Badewo Kayangan in Okura Pekanbaru Community from Treatment Rituals to Aesthetic Dance: Ecotourism - Afri Yenni; Agustina (Postgraduate, University of Mataram, 2023)
This research aims to explain the form and function of Badewo Kayangan as a healing ritual in the past and present for the people of Tebing Tinggi Okura. This research is qualitative research with a descriptive approach that understands the phenomenon of the research subject. The data in this research is information obtained through various sources, both sources obtained directly through interviews with sources who know about the Badewo Khayangan dance, video recordings, photographs, and data in the form of documentation. Apart from this data, it is also supported by data in the form of notes obtained during observations. The research findings are that Badewo Kayangan was originally a healing ritual used to cure various diseases, including those caused by supernatural forces in the Okura High Cliff area. As time went by, people began to ask Wak Damai to change Badewo Kayangan into the Badewo Kayangan dance. The movements contained in Badewo Kayangan are combined with new elements and realized in the form of a dance performance known as the Badewo Kayangan dance. Badewo Kayangan has two main roles, namely as a traditional healing ritual and as a means of performing arts or entertainment. By considering the potential of the Badewo Kayangan Tebing Tinggi Okura dance as a local cultural asset, this dance has the potential to become part of the tourism industry based on culture.